UJI FITOKIMIA DAN TOKSISITAS TERHADAP ARTEMIA SALINA DARI EKSTRAK METANOL JARINGAN DAUN MANGROVE RHIZOPHORA MUCRONATA - Ma’rifatul Jannah; Usman Usman (PROSIDING SEMINAR KIMIA, 2022)
Mangrove plants can produce bioactive compounds that have the potential to be developed into medicinal plants. Mangrove Rhizopora mucronata is one of the mangrove species that has bioactive compounds. This study aims to determine the content of secondary metabolites by conducting phytochemical tests and toxicity tests on Artemia salina (shrimp larvae) in the methanol extract of Rhizopora mucronata mangrove leaves. The sample used was Mangrove Rhizopora mucronata obtained from sambera mangrove trees from Muara Badak, East Kalimantan. Extraction was carried out using the maceration method, where samples of Rhizopora mucronata mangrove leaves were extracted with methanol for 3 x 24 hours. The methanol extract obtained was evaporated using a rotary evaporator. Furthermore, the methanol viscous extract was carried out by phytochemical test using color test method and toxicity test using BSLT. Based on the results of phytochemical tests, the methanol extract of mangrove leaves Rhizopora mucronata contains alkaloids and saponins. The toxicity of the methanol extract of Rhizopora mucronata mangrove leaves is in the moderate category with an LC50 of 48,165 ± 52,25 ppm. Rhizopora mucronata mangrove leaf extract contains active compounds that have the potential to be developed as alternative and anticancer drugs Keywords: Mangrove Rhizopora mucronata, methanol extract, active chemical content, toxicity